Actions of the Train Compiler in Non-Standard and Emergency Situations - Sulaymanov, S.; Talipov, M. M. (European Journal of Life Safety and Stability (2660-9630), 2021)
this article discusses the issues of the procedure of train compilers in the most frequently recurring non-standard and emergency situations.